Evaluation of Environmental Barium Concentration Biomonitoring in Tree Rings - Kaan Işınkaralar (Turkish Journal of Agriculture: Food Science and Technology, 2022)
The effect of barium element that can be extremely harmful heavy metal to human and environmental health in urban centers. The barium can cause various environmental pollution due to its anthropogenic accumulation in the environment. Also, it has negative effects on plants, animals, and humans through atmospheric deposition. All Barium (Ba) compounds are harmful heavy metals and they show a poisonous effect on the environment. Thus, it is crucial to determine the Ba concentration in plants grown in areas with high pollution in the landscape, park, and roadside. Biomonitoring with the tree species can be determined which is the best passive biomonitoring method with the tree rings formed by the effect of seasonal differences. The barium has been accumulated in the tree rings for a long time that can provide critical knowledge about the atmospheric barium deposition. The temporal and spatial variations of Ba concentration were analyzed with organs of Ailanthus altissima (Mill.) as biomonitors. This study results show that the outer bark of Ailanthus altissima (Mill.) is a convenient biomonitor for Ba deposition.